Modeling of the annual cycle of Melophagus Ovinus (L.) in two sheeps flocks of Patagonia, Argentina - Larroza, Marcela Patricia; Aparicio, Alejandro Gabriel; Raffo, Fernando; Cabrera, Raúl Francisco; Olaechea, Fermin (2018)
The ked Melophagus ovinus (L.), one of the most common obligate external parasites in sheep, is a recurrent problem in temperate sheep production areas worldwide. Modeling of its annual dynamics, which is lacking, can contribute to delineate integrated management strategies. We sampled ked density along a one-year period in two sheep farms of Northwest Patagonia, Argentina. In one farm with semi-intensive sheep management, we sampled 20 lambs and 10 adult Corriedale-cross sheep naturally parasitized prior to our study. In a second farm with extensive management, we sampled 10 Merino lambs, which we artificially infested in early autumn. We fitted bell-shaped curves to describe the annual ked population dynamics in each animal group and used global fitting to compare the models. In the two-cohort flock, the peak ked density in lambs was almost two-fold higher (Nmax=186 vs. 86) and occurred 1.5 months earlier (early August) than that in adult sheep; time span parameter was equal in both curves (SD≈64 days). In the artificially parasitized lambs, the ked population showed a ca. five-month lag period, after which density increased sharply to a peak of Nmax=155, reached well into spring (late October); the span of the model was SD=38 days. Based on the ked annual cycles modeled and considering the traditional sheep management practices, we suggest monitoring flocks at least twice a year: at pre-mating in mid-autumn and at the annual shearing in spring (pre-lambing shearing or traditional shearing). Ked detection and treatment at pre-mating can prevent keds from entering the exponential phase and the consequent sanitary and economic impacts. In case keds are detected, treatment after pre-lambing shearing may prevent infestation of newborn lambs. Monitoring at traditional shearing is also an opportunity for ked detection, although it could be hard since ked populations will be in a phase of advanced decline in both adult and young sheep. Future works that statistically model the annual population dynamics of keds, under well-defined conditions, may allow meta-analyses of the behavior of this widely distributed plague, especially under the accelerating climate and agricultural changes worldwide.